Bisphenol A: A Testicular Teratogen in Developing Rats During Prenatal and Early Postnatal Life - Tooba Khurshid, Rehana Rana, Shabana Ali, Huma Beenish, Ali Ahmed, Syeda Sara Bano (Journal of Islamic International Medical College, 2021)
Objective: To study the teratogenic effects of Bisphenol A on the testicular histogenesis of developing rat pups during prenatal and early postnatal life. Study Design: Laboratory-Based Randomized Control Trial. Place and Duration of Study: The present study was carried out at Anatomy Department of Islamic International Medical College Rawalpindi in association with National Institute of Health (NIH) Islamabad from September 2018 to September 2019. Materials and Methods: Eight weeks old 10 pregnant female rats were divided into 2 groups each containing 5 pregnant female rats. Pups were delivered by spontaneous vaginal delivery. Control group A was composed of 15 male rat pups from 5 pregnant female rats fed on the standard diet during pregnancy and lactation till day 21. Experimental group B was composed of 15 male rat pups from 5 pregnant female rats which were given 250μg/kg/day Bisphenol A subcutaneously during pregnancy and lactation till day 21. Results: Deterioration of histological parameters was significantly seen in group B. Tubule differentiation index(TDI) in group B was 69.22%; significantly reduced as compared to control group A. The modified Johnsen's criteria in group B was score 3 (in 33.3% rats ) and score 1 (in 26.6% rats) as compared to score 7 (in 100% rats) in control group A. 66.6% rats in group B showed severe (grade 4) and 26.6% rats showed moderate (grade 3) epithelial degeneration as compared to control group A. 46.6% rats in group B showed severe (grade 4) and 40% had moderate (grade3) congestion as compared to control group A.46.6% rats in group B showed severe (grade 4) vacuolization and 33.3% had moderate (grade3) vacuolization as compared to control group. Conclusion: The teratogenic effect of BPA on developing rat testes is evident when given during prenatal and early postnatal life. The teratogenicity of BPA may adversely affect spermatogenesis and male fertility.